Police Performance in Police Record Certificate Services at Tomohon Police Station - Sisca B. Kairupan; Pamela Liwe; Fitri H. Mamonto; Trifena Julia Kambey; Denny Maliangkay (Technium Social Sciences Journal, 2024)
The main aim of this research is to analyze and describe the performance of the police in SKCK services at Tomohon Police. The approach used is descriptive qualitative. The number of informants in this research was 10 people. Data collection techniques use observation, interviews and documentation. Data analysis through data collection, data reduction, data presentation and confirmation of conclusions. The research results based on the four research focus indicators show that: 1) the SKCK service performance of police employees is not optimal, resulting in slow work of employees; 2) Obstacles that occur, such as if there are many applicants who apply for SKCK, there can be a lot of queues and it takes quite a long time for each person, so it gives the impression that the service is slow and unsatisfactory and there are still many applicants who do not understand the online SKCK registration even though the steps have been explained; 3) There are still police employees who are not disciplined, such as those who are late coming to the office; 4) The public’s response regarding SKCK services is good and positive but they still receive constructive complaints, suggestions and complaints. It was concluded that the performance of the SKCK service for police employees was not optimal because there were still problems in the SKCK service. In performance management, it is important for superiors to measure, manage and improve the performance of police employees continuously.